Regulation of Vessel Permeability by TRP Channels - Genova, Tullio; Gaglioti, Deborah; Munaron, Luca (Frontiers in Physiology, 2020)
The vascular endothelium constitutes a semi-permeable barrier between blood and interstitial fluids. Since an augmented endothelial permeability is often associated to pathological states, understanding the molecular basis for its regulation is a crucial biomedical and clinical challenge. This review focuses on the processes controlling paracellular permeability that is the permeation of fluids between adjacent endothelial cells. Cytosolic calcium changes are often detected as early events preceding the alteration of the endothelial barrier function. For this reason, great interest has been devoted in the last decades to unveil the molecular mechanisms underlying calcium fluxes and their functional relationship with vessel permeability. Beyond the dicotomic classification between store-dependent and independent calcium entry at the plasma membrane level, the search for the molecular components of the related calcium-permeable channels revealed a difficult task for intrinsic and technical limitations. The contribution of redundant channel-forming proteins including members of TRP superfamily and Orai1, together with the very complex intracellular modulatory pathways, displays a huge variability among tissues and along the vascular tree. Moreover, calcium-independent events could significantly concur to the regulation of vascular permeability in an intricate and fascinating multifactorial framework.